Epidemiological study of patients attending anti-rabies vaccination clinic of tertiary care hospital of Southern Maharashtra, India - Kaware, Alka C.; Rokade, Hemlata M.; SK, Mangulikar (International Journal Of Community Medicine And Public Health, 2017)
Background: Epidemiology of animal bite is imperative for policy making, planning and effective implementation of prevention and control programme at local, state and national level. The objective was to study the epidemiology of patients attending anti-rabies vaccination clinic and to study treatment seeking behavior of patients attending anti-rabies vaccination clinic. Methods: A hospital based cross-sectional study was conducted in patients attending anti-rabies vaccination clinic of a tertiary care hospital in Solapur during January to December 2013. Detail history regarding socio-demographic profile, type of bites including site, duration, category of exposure, wound toilet, treatment, etc. was inquired. Results: Out of total 7371 patients screened, 71.75% were males and 28.25% were females. Maximum patients i.e. 52.31% were educated up to high school and 4.71% were illiterate. Majority of the patients i.e. 83.63 % were from urban areas. Dog was the most common (93%) biting animal and 34.72% animal bites were of category III. 70.99% injuries were of superficial type and 29.01% were deep wounds. Maximum number i.e. 44.35 % bites were on lower limb, 30.86% were on upper limb, 16.8% on head, neck, face and 7.99% on trunk. Around 40.54 % patients did nothing as pre-treatment management of wound. Anti-rabies vaccine was administered to 99.35% of cases and rabies immunoglobulin to 35.26% cases. Conclusion: Our study findings suggests that the majority of the patients were from urban set up inflicted upon by animal bites with poor knowledge regarding wound care and seeking early treatment.